2016
DOI: 10.1108/jaee-10-2013-0051
|View full text |Cite
|
Sign up to set email alerts
|

On the tax-accounting linkage in the European emerging context

Abstract: Purpose – The purpose of this paper is to investigate stakeholders’ salience on accounting and in particular to assess the magnitude of state influence in Romania, an emerging context. Design/methodology/approach – This research integrates stakeholders’ theory and an empirical approach based on a survey administrated to professional accountants as preparers of accounts on the financial reporting market. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…In U.S., the shifting of income is not a main issue as long as the resident country is not low tax or no-tax jurisdiction as long as dependence on intergovernmental assistance (Spencer, 2014) (Bharadwaj & Soni, 2007) (Tannewald, 2001) In Europe (EU), since the e-commerce tax was formally agreed in 2002, the key effects were already amended as follow: (1) non-EU organizations accounted for VAT, (2) EU organizations accounted for VAT using the reverse charge mechanism, (3) EU organizations exported outside the EU were not accounted for VAT, and (4) EU organizations supplying to non-business organizations accounted for VAT at the rate due in their own member state (Sinyor, 2002). Different concern derived from study about stakeholders' salience that found that accounting bodies, academics and business representatives should communicate effectively and constructively with the public structures with respect to enforcement of accounting regulations and the type of organizations involved (Deaconu & Cuzdriorean, 2016).…”
Section: Developed Countriesmentioning
confidence: 99%
“…In U.S., the shifting of income is not a main issue as long as the resident country is not low tax or no-tax jurisdiction as long as dependence on intergovernmental assistance (Spencer, 2014) (Bharadwaj & Soni, 2007) (Tannewald, 2001) In Europe (EU), since the e-commerce tax was formally agreed in 2002, the key effects were already amended as follow: (1) non-EU organizations accounted for VAT, (2) EU organizations accounted for VAT using the reverse charge mechanism, (3) EU organizations exported outside the EU were not accounted for VAT, and (4) EU organizations supplying to non-business organizations accounted for VAT at the rate due in their own member state (Sinyor, 2002). Different concern derived from study about stakeholders' salience that found that accounting bodies, academics and business representatives should communicate effectively and constructively with the public structures with respect to enforcement of accounting regulations and the type of organizations involved (Deaconu & Cuzdriorean, 2016).…”
Section: Developed Countriesmentioning
confidence: 99%
“…Romania is the second largest CEE country (after Poland) that is on its way to a market economy. Along with other modernization efforts, a number of accounting reforms have concerned the country's financial reporting model with the European Directives and/or with International Financial Reporting Standards (Albu et al, 2011), yet it remained highly connected to taxation (Deaconu and Cuzdriorean, 2016). MA was left at the discretion of organizational management for most of the transition period.…”
Section: Introductionmentioning
confidence: 99%
“…After the fall of communism around the early 1990s, the CEE region has provided 'unique societal quasi-experiments' where existing international business and management theories could be tested, and new theories could be developed (Meyer & Peng, 2005). The academic literature provides some insights into the use of accounting by SMEs (Albu et al, 2013;Chau et al, 2013;Deaconu & Cuzdriorean, 2016;Talpas, 2016;Tatoglu et al, 2016). Issues investigated so far include the financial reporting quality and the cost of debt of SMEs (Vander Bauwhede et al, 2015), the use of the International Financial Reporting Standard for SMEs (IFRS for SMEs) (Kaya & Koch, 2015;Perera & Chand, 2015), the alignment of accounting information systems in SMEs (Ismail & King, 2007), the resource organization and SMEs performance (Andersén & Samuelsson, 2016) or even the possible use of integrated reporting (Del Baldo, 2014).…”
Section: Introductionmentioning
confidence: 99%